The effect of fungi-origin probiotic Chrysonilia crassa in comparison to selected commercially used feed additives on broiler chicken performance, intestinal microbiology, and blood indices - Sugiharto, Sugiharto; Yudiarti, Turrini; Isroli, Isroli; Widiastuti, Endang; Wahyuni, Hanny Indrat; Sartono, Tri Agus (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objective of the current study was to investigate the influence of probiotic Chrysonilia crassa in comparison with zinc bacitracin, commercial probiotic Bacillus subtilis, and herbal medicine waste on growth, intestinal microbiology, and blood indices of broilers. Materials and methods: Three hundreds of Lohmann day-old chicks were allocated to control diet (basal diet; CONT), basal diet with antibiotic zinc bacitracin (AZB), basal diet with B. subtilis (PROB), basal diet with C. crassa (PROC), and basal diet with herbal medicine waste (HERBW). Sample collections were conducted on day 34 of the experiment. Results: PROB showed greater (P<0.05) body weight than CONT chicks. Leukocytes and lymphocytes numbers were higher (P<0.05) in HERBW than in birds of other treatments. Compared to CONT and HERBW, PROC birds showed higher (P<0.05) level of vaccine titer to Newcastle disease virus. CONT had lower (P<0.05) and higher (P<0.05) total protein and globulin, and the ratio of albumin to globulin (A/G ratio) in serum, respectively, compared to other chicks. Higher level (P<0.05) of albumin was observed in PROB relative to CONT and PROC. Lower uric acid (P<0.05) was seen in PROC when compared with CONT and PROB. PROC had higher (P<0.05) aspartate aminotransferase than AGP, PROB, and HERBW. Ileal coliform was decreased (P<0.05) in PROB and PROC, relative to CONT and HERBW. Conclusion: Probiotics were capable of improving the growth, immune responses, and intestinal bacterial populations of broilers. The effects of probiotics C. crassa corresponded to that of commercial probiotic B. subtilis and antibiotic growth promoters. http://doi.org/10.5455/javar.2018.e284